World Public Sector Report 2021 - United Nations Department of Economic; Social Affairs (United Nations, 2021)
Five years after the start of the implementation of the 2030 Agenda for Sustainable Development and its Sustainable Development Goals (SDGs), governance issues remain at the forefront. The COVID-19 pandemic has highlighted even more the importance of national institutions for the achievement of the SDGs. The World Public Sector Report 2021 focuses on three dimensions of institutional change at the national level. First, it documents changes in institutional arrangements for SDG implementation since 2015. Second, it assesses the development, performance, strengths and weaknesses of follow-up and review systems for the SDGs. Third, it examines efforts made by governments and other stakeholders to enhance the capacity of public servants to implement the SDGs. Based on in-depth examination of institutional arrangements for SDG implementation in a sample of 24 countries in all regions, the report aims to draw attention to the institutional dimension of SDG implementation and provide lessons for national policymakers in this regard. The report also takes stock of the impacts of the COVID-19 pandemic on national institutions and their implications for delivering on the 2030 Agenda. The e-book for this publication has been converted into an accessible format for the visually impaired and people with print reading disabilities. It is fully compatible with leading screen-reader technologies such as JAWS and NVDA.